Generalized Multiprotocol Label Switching convergence NETWORKS IN THE SCHEME - Eriek Eriek Orlando (Majalah SIKOMTEK, 2005)
Convergence of Internet and telecommunications, with applications in it that more and morebandwidth with QoS penqaturan it finally takes the network and element in it which gave fullsupport to the preservation and improvement of network performance. If the first object thatbandwidth is always a predictable, so this time some applications already require schemes"bandwidth on demand". On the other hand the network efficiency by leveraging publicnetworks to be the main constraint in the deployment of services, especially for commercialpurposes. Trasnport technology is required which not only facilitate the best path routing anddiscovery, yet can also accommodate non-package existing technologies. The authordescribes the development of GMPLS today, particularly in the scheme of networkconvergence with other transport technologies. Also described brieflyabout the relationship pengembanngannya MPLS as the base.